The Impact of Father's Absence on Psychological Conditions in Children from Commuter Marriage Families - Evi Syafrida Nasution; Anizar Rahayu; Anita Cameliana (Pelopor Publikasi Akademika, 2023)
This study aims to investigate the impact of fatherlessness on the psychological development of children from commuter marriage families. This research uses a qualitative approach with a case study method. The subject of this study is an 8-year-old child. Data collection techniques in this study include interviews, observations, and psychological tests. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. The data's validity is tested using source triangulation techniques. Based on the research results, the impact of fatherlessness on the psychological development of the child shows that: S does not get quality time with his father to engage in play activities because the father works out of town and returns only once a year. S's father verbally abuses his wife, indicating the loss of the father's role as a source of love and protection from harm. S's father makes rules and decisions within the house without first consulting his wife and children. Every decision made by the father must be followed by the mother and children, or else the father becomes angry. S's father believes that raising and educating children is solely the mother's responsibility, and a husband's role is only to provide for the family financially. S's mother is unable to establish the father's presence in the children's lives. S has difficulty following lessons at school and adapting to school life, as he always needs to be accompanied by his mother. When playing, S only interacts with close friends he already knows.